Cu(i)/sucrose-catalyzed hydroxylation of arenes in water: the dual role of sucrose. Issue 39 (29th September 2020) - Watanabe, Kohei; Takagi, Mio; Watanabe, Ayako; Murata, Shigeo; Takita, Ryo
Abstract : Copper(i )/sucrose-catalyzed hydroxylation of aryl halides in neat water has been developed. The dual role of sucrose, the reaction pathway, and the high selectivity were investigated using a combination of experimental and theoretical techniques. Abstract : A protocol for the hydroxylation of aryl halides catalyzed by copper(i ) and sucrose in neat water has been developed. The dual role of sucrose, the reaction pathway, and the high selectivity for hydroxylation were investigated using a combination of experimental and theoretical techniques.